The Science and Practice of Stress Management: A 2026 Comprehensive Review - Shambhu, Shiv (International Journal of Social Sciences and Management, 2026)
Stress is a pervasive phenomenon affecting individuals across cultures, professions, and age groups. In 2026, stress remains a primary catalyst for chronic illness. This article reviews the concept of stress, its physiological and psychological impacts, and evaluates various stress management strategies, evolution of stress from a survival mechanism to a modern epidemic. By synthesizing findings from recent literature, the paper highlights effective interventions, emerging approaches, and gaps in current research. It evaluates traditional interventions alongside emerging digital therapeutics and neurofeedback technologies, providing a framework for holistic stress reduction. Int. J. Soc. Sc. Manage. Vol. 13, Issue-1: 3-7.